Literature Review : Pengalaman Perawat Terkait Pelaksanaan Cultural Competence Di Ruang Intensive Care Unit - Yeni Binteriawati; Tuti Pahriah; Aan Nuraeni (Faletehan Health Journal, 2020)
Intensive Care Unit (ICU) is an area of ​​care activity and well designed to treat critical conditions, nurses must have cultural competence. Culture participates in health values, beliefs, behavior and situational judgments. If left untreated will result in negative social and clinical consequences, unclear environment, confusion, messages not delivered, patient ignorance, delay in informed consent and low quality of care. The purpose of this study is to describe the experience of nurses related to the implementation of Cultural Competence in the ICU from research that has been done. The method used by searching electronic articles consists of qualitative studies collected from electronic databases such as Medline, Google Scholar, Science Direct, PubMed and Proquest using relevant MeSH keywords: Cultural Competence, Intensive Care Unit, and Nursing. Articles selected according to the SPIDER criteria, published in 2012-2018. Evaluation of articles uses critical appraisal and PRISMA guidelines. From the results of the literature search conducted, as many as 7 (seven) related articles were found and met the criteria. The results of the themes that emerged related to the implementation of cultural competence include the involvement of the family in the care process, using translators, maintaining a multicultural team, communication procedures, and clear diagnosis and recognizing cultural diversity.